An Emerging Role of TIM3 Expression on T Cells in Chronic Kidney Inflammation - Lu, Can; Chen, Huihui; Wang, Chang; Yang, Fei; Li, Jun; Liu, Hong; Chen, Guochun (Frontiers in Immunology, 2022)
T cell immunoglobulin domain and mucin domain 3 (TIM3) was initially identified as an inhibitory molecule on IFNγ-producing T cells. Further research discovered the broad expression of TIM3 on different immune cells binding to multiple ligands. Apart from its suppressive effects on the Th1 cells, recent compelling experiments highlighted the indispensable role of TIM3 in the myeloid cell-mediated inflammatory response, supporting that TIM3 exerts pleiotropic effects on both adaptive and innate immune cells in a context-dependent manner. A large number of studies have been conducted on TIM3 biology in the disease settings of infection, cancer, and autoimmunity. However, there is a lack of clinical evidence to closely evaluate the role of T cell-expressing TIM3 in the pathogenesis of chronic kidney disease (CKD). Here, we reported an intriguing case of Mycobacterium tuberculosis (Mtb) infection that was characterized by persistent overexpression of TIM3 on circulating T cells and ongoing kidney tubulointerstitial inflammation for a period of 12 months. In this case, multiple histopathological biopsies revealed a massive accumulation of recruited T cells and macrophages in the enlarged kidney and liver. After standard anti-Mtb treatment, repeated renal biopsy identified a dramatic remission of the infiltrated immune cells in the tubulointerstitial compartment. This is the first clinical report to reveal a time-course expression of TIM3 on the T cells, which is pathologically associated with the progression of severe kidney inflammation in a non-autoimmunity setting. Based on this case, we summarize the recent findings on TIM3 biology and propose a novel model of CKD progression due to the aberrant crosstalk among immune cells.